Making International Law without Agreeing What It Is - Tai-Heng Cheng (Washington University Global Studies Law Review, 2011)
The article examines how international law functions despite of decision-makers' different conceptions towards the international legal theory. It highlights the invasion of the U.S. on the construction of a wall by Iraq and Israel around Palestine, which depicts how outcomes of a legal nature can be obtained regardless of different conceptions of international law. It discusses the fragmentation of international legal theory using positivism and policy-oriented jurisprudence.
Keywords: International law -- Interpretation & construction; Legal positivism; International law -- Philosophy; Jurisdiction (International law); International courts